A fuzzy control method of nano material forming temperature based on PLC. (19th March 2022) - Yin, Huangyan
In order to overcome the problem of low temperature monitoring accuracy and forming temperature control accuracy of nano materials, a new nano material forming temperature control method based on PLC is proposed in this paper. Firstly, the steady-state gain of nano material forming temperature is calculated, and the first step response curve of forming temperature is calculated. Secondly, particle swarm optimisation algorithm is introduced to optimise the control parameters of PLC controller. Finally, the fuzzy control algorithm is used to discretise the nano material forming temperature control, and the nano material forming temperature control is completed. The experimental results show that compared with the traditional control method, the moulding temperature control result of this method is basically consistent with the actual moulding temperature, and the maximum control error is only 0.1°C.